Prevalence and Factors Associated With Adolescent Pregnancy Among an Indigenous Ethnic Group in Rural Nepal: A Community-based Cross-sectional Study - Kusumsheela Bhatta; Pratiksha Pathak; Madhusudan Subedi (Korean Society for Preventive Medicine, 2024)
Objectives: The Chepang people, an indigenous ethnic group in Nepal, experience substantial marginalization and socioeconomic disadvantages, making their communities among the most vulnerable in the region. This study aimed to determine the prevalence and factors associated with adolescent pregnancy in the Chepang communities of Raksirang Rural Municipality, Makwanpur District, Bagmati Province, Nepal. Methods: A cross-sectional study was conducted from October 2022 to April 2023 among 231 Chepang women selected using simple random sampling from Raksirang Rural Municipality. A semi-structured questionnaire was used for interviewing the mothers. Bivariate and multivariate logistic regression analyses were performed, using odds ratios with 95% confidence intervals (CIs). Variables with a variation inflation factor of more than 2 and a p-value of more than 0.25 were excluded from the final model. Results: The study revealed that the prevalence rate of adolescent pregnancy among Chepang women was 71.4% (95% CI, 65.14 to 77.16). A large percentage of participants (72.7%) were married before the age of 18 years. Poor knowledge of adolescent pregnancy (adjusted odds ratio [aOR], 10.3; 95% CI, 8.42 to 14.87), unplanned pregnancy (aOR, 13.3; 95% CI, 10.76 to 19.2), and lack of sex education (aOR, 6.57; 95% CI, 3.85 to 11.27) were significantly associated with adolescent pregnancy. Conclusions: The prevalence of adolescent pregnancy among the Chepang community was high. These findings highlighted the importance of raising awareness about the potential consequences of adolescent pregnancy and implementing comprehensive sexuality education programs for preventing adolescent pregnancies within this community.